Critical Analysis of Cooperative Learning in Organizations: With Special Emphasis on Employee Satisfaction (Journal of Asian Development Studies, 2024)
The study determines the influence of employee autonomy and organizational climate on cooperative learning and its ultimate effect on employee satisfaction and work performance. In organizations, problems arise frequently, which makes creativity and teamwork mandatory. The sample size includes 127 experts in information system development and 34 managers and customers in software development companies in the regions of Islamabad and Peshawar. The LISREL software is used for statistical data analysis because of the study's structure equation model. Relative chi-square, standardized RMSR, GFI, AGFI, NFI, CFI, Cronbach alpha, t-value, factor loading, and path-coefficient explain the relationship among variables. The results signify that employee autonomy and a favorable organizational climate support cooperative learning, and the produced tacit knowledge enhances work satisfaction and creates a state of synergy. The study's findings are specifically more spirited for the practitioners working in the challenging environment of software houses. Moreover, the survey findings encourage innovation and create new ideas, essential for enhancing organizational productivity.